Contamination du lac Saint-Pierre (fleuve Saint-Laurent) par certains polluants organiques et inorganiques - Langlois, C.; Sloterdijk, H. (Revue des sciences de l'eau, 1989)
L'étude s'inscrit dans le cadre d'un programme de surveillance de la dispersion des substances toxiques dans le fleuve Saint-Laurent. Elle vise à identifier la nature et le cheminement des substances toxiques dans différents compartiments du lac Saint-Pierre. D'une superficie totale de plus de 400 km2, ce lac est un élargissement du fleuve et son bassin de drainage inclut la région métropolitaine de Montréal et la région inter-nationale des Grands lacs. L'échantillonnage a porté sur l'eau, les matières en suspension, les sédiments de fond, les poissons adultes (entiers, chairs, foie, oeufs et gonades) et les poissons juvéniles (âge 0+). Des analyses chimiques ont été effectuées pour les métaux, les pesticides organochlorés, les biphényles polychlorés (PCB), les hydrocarbures aromatiques polycycliques (PAH) et les chlorobenzènes. Les résultats indiquent que la contamination du milieu aquatique par les substances toxiques est très significative. Les contaminants majeurs retrouvés dans les divers compartiments sont l'arsenic, le mercure, le plomb, les biphényles polychlorés (PCB) et les différentes formes de DDT. Les concentrations excèdent fréquemment les critères de qualité pour le mercure dans les chairs de poissons, le plomb dans l'eau et les sédiments et les PCB dans plusieurs compartiments analysés. Plusieurs pesticides organochlorés ont été détectés dans l'eau, grâce à la technique d'échantillonnage à grand volume. Cette technique permet d'estimer 1a concentration de fond et le bilan massique annuel d'un polluant. Les poissons entiers et le foie de lottes constituent par ailleurs des indicateurs de choix de la présence et de l'étendue de la contamination par les substances toxiques bioaccumulables, alors que les sédiments de fond et les poissons juvéniles permettent d'étudier leur répartition spatiale. Sauf pour le mercure, les concentrations dans les chairs sont un mauvais indicateur de la contamination du milieu; la moyenne et la variabilité des teneurs en PCB et pesticides organochlorés y sont très faibles. As part of a monitoring program on pollutants dispersion in the St. Lawrence river, a study was conducted in 1986 on the fate and pathways of toxic substances in Lake St. Pierre. This enlargement of the St. Lawrence drains the Montreal metropolitan area and the international great lakes region. Water, sediments and fish were collected and analyzed. Water was sampled following the conventional method (1 l) or passed through an XAD-2 resin column (70 l of centrifuged water). Suspended sediments were collected by centrifuging 2000 l of water. Bottom sediments were collected by retaining the top layer of a grab sample taken using an Eckman dredge. Young-of-the-year forage fishes (Spottail Shiner and Yellow Perch) were captured using a seine whereas adult fishes (Northern Pike, Walleye, Brown Bullhead, Yellow Perch, White Sucker, Bowfin and Burbot) were captured using hoop-nets and gill-nets. All samples were analyzed for metals, organochlorine pesticides, PCBs, PAHs and chlorobenzenes. Fishes were analyzed as homogenate of whole individuals (young-of-the-year and adult) and as homogenate of fish flesh. Results indicate that the level of contamination by toxic chemicals is highly significant. The major contaminants found in the different media are arsenic, mercury, iron, PCBs and various derivatives of DDT. The concentration frequently exceeds the guidelines suggested for mercury in fish flesh, iron in water and sediments and PCBs in most compartments analysed. Several organochlorine pesticides have been detected in water using Large Volume Sampling technique. This technique allows estimation of background concentration and annual mass balance for specific pollutants. Whole fishes and Burbot's livers are good indicators of the presence and concentration range of bioaccumulating toxic substances. Bottom sediments and juvenile fishes are good indicators of spatial distribution of toxic chemicals in the lake. PCB's highest concentrations are found in adult whole fish samples (mean of 1030 µg/kg). Bottom sediments concentrations show a higher mean (112 µg/kg) than for Lake St. Louis, located upstream of Montreal. Some PAHs and chlorobenzenes are occasionally detected in various compartments.